A New Linear Companding Transform to Reduce the PAPR in OFDM System under Rayleigh Distribution - Dr. Gopala Krishnan, Venkatesh Thota, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Large amplitude fluctuations causeserious issues in orthogonal frequency-division multiplexing (OFDM) signals, when a nonlinear power amplifier (NLPA) has been utilized. These large amplitude fluctuations are known as peakto- average power ratio (PAPR), which is a major disadvantage of OFDM system. To resolve this issue, one must need to reduce these large amplitude fluctuations in order to achieve higher data rates and to improve system performance. A well-known method for reducing the PAPR is companding transform (CT). It doesn’t have any restrictions on system parameters such as frame format, number of subcarriers and type of constellation used.Recently, a linear nonsymmetrical companding transform (LNST) has been proposed which has a superior performance than the transformations based on logarithmic transforms such as μ-law companding. Here, a new linear companding transform (LCT) with Rayleigh distribution (RD) has been implemented with more design flexibility than LNST by introducing two inflexion points. Experimental results show that the proposed transform has a better PAPR reduction and bit error rate (BER) performance than LNST with better power spectral density (PSD).